Primary cutaneous histoplasmosis developed in the penis of an immunocompetent patient() - Paixão, Mauricio (An Bras Dermatol, 2015)
A 70-year-old male presenting a 3-month history of genital painless erythematous nodules in the balanopreputial sulcus was referred to our service. Histopathological exam presented a chronic dermatitis with epithelioid granulomas and Grocott staining revealed numerous fungal structures with a suggestive morphology of Histoplasma sp. Cultures evidenced Histoplasma capsulatum var. capsulatum. Treatment with oral itraconazole led to complete remission of lesions.